2011
DOI: 10.3748/wjg.v17.i24.2958
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of mutant bacterial cytosine deaminase gene for colon cancer

Abstract: The bCD mutant D314A enhanced significantly antitumor activity in human colon cancer xenograft models, which provides a promising approach for human colon carcinoma therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Kaliberova et al (2008), reported the sequence of a mutant, bCD-D314A, which showed a significant specificity towards 5-FC with a lower IC 50 in comparison to wt-bCD. This mutant has been successfully used in combination with low dose radiation to reduce tumor sizes in various cancer models [91, 92]. Another mutant, reported by Fuchita et al (2009), has showed the most desirable features for suicide gene therapy in terms of significant shift to 5-FC, decrease in IC 50 and an outstanding bystander effect compared to wt-CD[93].…”
Section: Enzyme/prodrug Systems: From Bench To Bedmentioning
confidence: 99%
“…Kaliberova et al (2008), reported the sequence of a mutant, bCD-D314A, which showed a significant specificity towards 5-FC with a lower IC 50 in comparison to wt-bCD. This mutant has been successfully used in combination with low dose radiation to reduce tumor sizes in various cancer models [91, 92]. Another mutant, reported by Fuchita et al (2009), has showed the most desirable features for suicide gene therapy in terms of significant shift to 5-FC, decrease in IC 50 and an outstanding bystander effect compared to wt-CD[93].…”
Section: Enzyme/prodrug Systems: From Bench To Bedmentioning
confidence: 99%
“…The same AdbCD-D314A vectors were also used to treat pancreatic cancer cells and similar results with mutant D314A displaying increased tumor killing in vitro and in vivo were seen [79]. Deng et al (2011) showed similar improvements using human colon cancer xenograft models after lentiviral delivery of bCD-D314A and 5FC treatments [80]. …”
Section: Suicide Gene/prodrug Therapy For Cancermentioning
confidence: 90%
“…4. Also, dosing of 5-FC might have been suboptimal under our current regime applying a 5-FC standard dose of 500 mg/kg body weight, which is quite often used in mouse xenograft tumor models (You et al, 2009;Deng et al, 2011). However, in a recent preclinical study (Erbs et al, 2008) animal groups treated with adenovirus-based vectors (Ad-FCU1) exhibited statistically significant differences in tumor sizes between the group treated with Ad-FCU1 plus 5-FC and the other groups only when 5-FC was given at 1,000 mg/kg body weight per day.…”
Section: Discussionmentioning
confidence: 99%